The effects of high-velocity hamstring muscle training on injury prevention in football players - Kamandulis, Sigitas; Cadefau, Joan Aureli; Snieckus, Audrius; Mickevicius, Mantas; Lukonaitiene, Inga; Muanjai, Pornpimol; Satkunskiene, Danguole; Molina, Victor; Blas Foix, Xavier de; Conte, Daniele (Frontiers in Physiology, 2023)
Background: Explosive and fast body movements, sprints, jumps and quick changes of direction, which are characteristic of the football training, place considerable strain on the hamstring muscles. Due to the high occurrence of hamstring injuries, new preventive strategies are required that focus on high-velocity training.The purpose was to assess the effectiveness of high-velocity elastic-band training in reducing the occurrence of hamstring injuries in football players.Methods: Male football players from 15 teams (n = 319) playing in national competitions participated in this study. The players were involved in a five-week exercise period in either the intervention group (INT) or the control group (CON), with a follow-up period of 4 months where hamstring injuries and exposure time were recorded. The INT group had two to three sessions per week of elastic-band training with low-load, highvelocity leg curls while lying prone; the CON group performed self-paced football-specific drills.The incidence rate of hamstring injuries was 6.5% in the INT group (8 out of 123 players) and 9.2% in the CON group (18 out of 196 players). Although the INT group showed almost 1/3 reduction in hamstring injury incidence compared to the CON group, the difference was not statistically significant (p>0.05). Moreover, no differences (P > 0.05, odds ratio [OR]= trivial-to-small) in distribution between the groups were found in hamstring injury characteristics (leg dominance and mechanism) except for the distribution of injuries that occurred during matches or training (P = 0.036; OR = 6.14, moderate).The program of high-velocity elastic-band training did not prove to be effective in preventing hamstring muscle injuries in football players despite displaying some positive indications that could be considering when creating injury prevention programs.